INTERNATIONALIZATION OF THE COSMETIC INDUSTRY WITHIN THE CONTEXT OF DIGITAL TRANSFORMATION - Agner, Julia Wiedermann; Wernecke Fumagalli, Luis André (Caderno PAIC, 2023)
After the phenomenon of globalization spread all over the world, which has its origins back in the last century, many companies underwent numerous changes to fit within the new reality, idealizing the process of Internationalization. Since the last decades, the usage of technology has created the possibility of development within business, as well, through Digital Transformation. Apart from that, it is possible to affirm that the Cosmetic Industry has shown enormous growth during recent years, influenced by the idealistic beauty standards, embracement of self-care and strong Digital influence. This paper aims to analyze the Internationalization process of cosmetic companies in the context of Digital Transformation, additionally to the impacts of Global Marketing Strategies within International companies. To achieve this goal, exploratory and quantitative research was conducted using bibliographic and documentary material to obtain all of the necessary information and data. It was possible to observe that there is still a lack of information on that currently, making the development of more studies necessary. However, regarding the used materials, it was feasible to conclude that the Internationalization of companies can be possibly potentialized by the application of Digital Transformation simultaneously. In that same sense, conclusions also revealed the importance behind Internationalization strategies when it comes to the cosmetic businesses nowadays, as well as the relevance of Global Marketing Strategies. It is possible to declare that, given the objective of this paper being to comprehend the aspects of cosmetic company’s Internationalization within Digital transformation, it was possible to observe the impact provided by both processes alongside Internationalization.